Strategy In Public Service - Novayanti Sopia Rukmana; Saddam Husain Thamrin (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This study aims to determine the implementation of Know Your Customers (KYC) and Citizen Charter (Service Contract) strategies in increasing employee responsiveness in collecting retribution for Bone Regency. The type of research used is descriptive qualitative. Data collection used observation techniques, interviews, and documentation. The analysis technique is carried out through data collection, data reduction, data presentation, and concluding. The results of this study indicate that the implementation of the public service responsiveness strategy of Bone Regency in collecting retribution is considered to be less responsive based on each of the 3 indicators of the two responsive strategies, there is one indicator on the Know Your Customers strategy which is considered not good, namely approach, while two other indicators are considered good, namely (surveys, observations, interviews) and know customers. The indicators on the three Citizen Charter strategies (Service Contracts) are considered to be still not good, namely service users as the centre of attention, service contracts, and system determination. Of course, there are still shortcomings that need attention, namely paying more attention to the needs of traders, following up on merchant complaints quickly, and providing services according to existing regional regulations. If this is allowed to continue, it will harm the implementation of public services in the future, bearing in mind that the increasing needs of traders must be supported by managers who are alert and responsible for their main tasks and functions, so that responsive services can be created.